Nebie low-cost and portable nebulizer kit for the low-income individuals - Arciaga, Reynaflor Estabillo
Asthma is a chronic respiratory condition in which the person's airway become narrowed, resulting to difficulty in breathing. Asthma attack is triggered by allergens and environmental conditions such as smoke, smog and molds and is typically characterized by coughing, wheezing, and shortness of breath. There is currently no cure for this disease. All medications of this disease focus on controlling and easing asthma attacks. Drugs are usually injected and inhaled. Examples of injected drugs are Omalizumab and steroids, though there are also inhaled steroids. Most of the injected medications for asthma are used for asthma prevention, and is quite expensive than the inhaled ones. Moreover, examples of inhaled drugs are bronchodilators such as albuterol and salbutamol, which are usually used for relieving attacks. Inhaled drugs are used with a nebulizer or inhaler. A nebulizer is an expensive device which transforms the liquid drug into a mist to be inhaled by the patient. It is easier to use than inhaler because you just need to breathe and inhale. In addition, it can be able to mix 2 or more asthma drugs. One problem with nebulizer is it is electric-powered and is so bulky, making it hard to use when outside home. Asthma is one of the leading sources of deaths in the Philippines and the world. According to World Health Organization, 12% of Philippines population of 90 million has asthma. Because asthma cannot be cured by this time, it is one of the most difficult and expensive illness one can ever have. Additionally, this respiratory disease can affect the patient's emotional and social condition. An individual may develop fear, anxiety, loss of control, and hyper vigilance. Low-income individuals living in squalor areas have a high chance of getting this disease because of their exposure to allergens such as molds, dust, smog, fumes, and smoke. Since asthma is a lifetime disease and requires a continuous medication, low-income individuals may find it hard to control this illness. Patients can overcome this situation by always having a nebulizer kit by his or her side. But how can this happen if nebulizers are so bulky? How can poor people afford this gadget if it is so expensive? Given that low-income individuals are laborers, how can they do their job well if their movements are restricted because of their fear of an event of asthma attack? Having all these in mind, my proposal to solve this dilemma is nebie. Nebie caters the needs of the low-income individuals by providing a nebulizer with high-end technology with more economical materials and energy source. It uses vibrating mesh and crank technology to achieve a more portable nebulizer that the user can bring during work. With nebie, low-income individuals with asthma can now work without worry of asthma attack.